Overview of the Hepatitis B Epidemiology and Vaccination among Healthcare Workers (المجلة الدولية للبحوث العلمية, 2023)
Introduction: Healthcare workers (HCWs) who are at high risk for HBV infection, have been recommended to receive the HB vaccine for over 20 years. This review aimed to highlight the enablers and obstacles facing the universal coverage of hepatitis B epidemiology and vaccination among healthcare workers. Methods: A search was conducted using the following terms related to hepatitis B, vaccination, and healthcare workers in Africa: hepatitis B, hepatitis B virus, vaccination, immunization, healthcare workers, health workers, and health personnel. This review included cross-sectional, case-control, and cohort studies. Studies in English or French from any location were selected. A search was conducted for articles published from 1970 to 2022 in PubMed and the Excerpta Medica Database (Embase) using search terms related to hepatitis B and healthcare workers. Results: This study analyzed 25 cross-sectional studies on healthcare workers (HCWs) in African countries to determine the prevalence of hepatitis B vaccination. The majority of the studies were conducted in hospitals and included HCWs from West and East Africa. After assessing the quality of the studies, 5 (14.3%) were found to be of high quality, 17 (77.1%) were of moderate quality, and 3 (8.6%) were of low quality. The proportion of HCWs who were fully vaccinated against hepatitis B varied widely, ranging from 0.8% in Rwanda to 72.0% in Libya. The overall pooled full vaccination coverage among HCWs in Africa was 24.7%. Subgroup analyses showed significant variation in vaccination coverage among HCWs in different regions of Africa and Asia, with the highest coverage in North Africa and the lowest in Central and East Africa. Conclusions:  Healthcare workers (HCWs) are at higher risk of infection with Hepatitis B virus (HBV) compared to individuals who do not work in hospitals, with frequencies of infection up to 4 times higher. HBV can be transmitted between patients and HCWs, as well as between HCWs and their relatives, contributing to the ongoing chain of transmission.